Direct observation of room-temperature high-level triplet–triplet annihilation process in 1%rubrene-doped OLEDs with a CzDBA sensitizer - Tang, Xiantong; Pan, Ruiheng; Guan, Xinyi; He, Yanjun; Jiang, Sha; Wang, Yongjie; Zhou, Xianju; Xiong, Zuhong (Applied physics letters, 2024)
Using the magneto-electroluminescence as a sensitive and fingerprint probing tool, a “hot exciton” channel, named the high-level triplet–triplet annihilation (HL-TTA or T2T2A, T2 + T2 → Sn → S1 → S0 + hv) process from the high-lying triplet (T2) to the lowest singlet states, is observed in 1%rubrene-doped organic light-emitting diodes with a thermally activated delayed fluorescence sensitizer of 9,10-bis(4-(9H-carbazol-9-yl)-2,6-dimethylphenyl)-9,10-diboraanthracene (CzDBA) at room temperature. The addition of a sensitizer simultaneously promotes the Dexter energy transfer channels of host-sensitizer and sensitizer-guest triplets, thereby increasing the amounts of T2 states and inducing the occurrence of the HL-TTA process. Additionally, the HL-TTA enhances with the increase in the bias current and decreases with lowering the working temperature, which is consistent with the current dependence of the conventional low-level TTA (T1T1A, T1 + T1 → S1 + S0) process but contrary to its temperature dependence. More interestingly, the high concentration of CzDBA induces the H-type aggregation of rubrene molecules, promoting the singlet fission process but suppressing the HL-TTA process. These findings enrich the physical understanding of hot exciton channels and provide ideas for the preparation of high-performance devices.